Rhizosphere microbial community enrichment processes in healthy and diseased plants: implications of soil properties on biomarkers - Deng, Yong; Kong, Wuyuan; Zhang, Xiaoming; Zhu, Yi; Xie, Tian; Chen, Ming; Zhu, Li; Sun, Jingzhao; Zhang, Zhihua; Chen, Chaoyong; Zhu, Chongwen; Yin, Huaqun; et al. (Frontiers in Microbiology, 2024)
Rhizosphere microorganisms regulate plant growth and development, and their distribution is likely influenced by plant health states. In this study, the response of rhizosphere bacteria and fungi of healthy and diseased plants compared to bulk microbe were analyzed using high-throughput sequencing. This was done to understand the adaption strategies of plant under Potato virus Y (PVY) infection from a microbial perspective. We found that the diversity and community structure of bacteria and fungi varied between bulk and rhizosphere soils, but not between healthy and diseased rhizosphere soils. LEfSe analysis showed the significant differences on bacterial and fungal community compositions and identified Roseiflexaceae, Sphingomonas, and Sphingobium as the bacterial biomarkers of bulk (BCK), healthy rhizosphere (BHS), and diseased rhizosphere (BIS) soils, repectively; Rhodotorula and Ascomycota_unidentified_1_1 were identified as the fungal biomarkers of bulk (FCK) and healthy rhizosphere (FHS) soils. Bacterial networks were found to be more complex and compact than fungal network, and revealed the roles of biomarkers as network keystone taxa. PVY infection further increased the connectedness among microbial taxa to improve rhizosphere microbial community stability and resistance to environmental stress. Additionally, water content (WC) played apparent influence on bacterial community structure and diversity, and pH showed significant effects on fungal community diversity. WC and pH were key factors affecting the biomarkers of bacterial rhizosphere communities, whereas the biomarkers of bulk bacterial were significantly affected by soil nutrient, especially for Sphingobium. Overall, the rhizosphere microbial community enrichment processes were different between healthy and diseased plants by changing the community compositions and identified different biomarkers. These findings provide insight into the assemblage of rhizosphere microbial communities and soil physicochemical properties, which enhances our understanding of the construction of an artificial core root microbiota to promote plant growth and resistance.